An Improved Digital Evidence Acquisition Model for the Internet of Things Forensic I: A Theoretical Framework - Harbawi, Malek; Varol, Asaf (Ieee, 2017)
Digital evidence plays a vital role in determining legal case admissibility in electronic-and cyber-oriented crimes. Considering the complicated level of the Internet of Things (IoT) technology, performing the needed forensic investigation will be definitely faced by a number of challenges and obstacles, especially in digital evidence acquisition and analysis phases. Based on the currently available network forensic methods and tools, the performance of IoT forensic will be producing a deteriorated digital evidence trail due to the sophisticated nature of IoT connectivity and data exchangeability via the things. In this paper, a revision of IoT digital evidence acquisition procedure is provided. In addition, an improved theoretical framework for IoT forensic model that copes with evidence acquisition issues is proposed and discussed.
5th International Symposium on Digital Forensic and Security (ISDFS) -- APR 26-28, 2017 -- Tirgu Mures, ROMANIA
Keywords: digital evidence acquisition; digital forensic; improved digital forensic; IoT; last-on-scene